Congenital diarrhea and enteropathies caused by a heterozygous mutation in the GUCY2C gene: a rare case report - Yuan, Chuanjie; Lyu, Juanjuan; Sun, Xiaomei; Wu, Jin; Liu, Ying (Frontiers in Pediatrics, 2026)
ObjectivesThis report presents a rare case of congenital diarrhea and enteropathies in a Chinese infant caused by a heterozygous mutation in the GUCY2C gene.Case presentationA male infant was born prematurely with a history of polyhydramnios and prenatal intestinal dilation. He developed persistent abdominal distension, secretory diarrhea, metabolic acidosis, severe electrolyte imbalances, and failure to thrive. Whole-exome sequencing identified a heterozygous mutation in GUCY2C (c.2356T > C, p.Y786H), classified as likely pathogenic. The patient also exhibited intestinal malrotation but did not require surgical intervention. Management included total parenteral nutrition, transition to an amino acid-based formula, and extensive electrolyte supplementation. At the 72-month follow-up, he exhibited normal growth and complete resolution of gastrointestinal symptoms.ConclusionsA heterozygous mutation in the GUCY2C gene (c.2356T > C) was identified as the cause of this rare congenital diarrheal disorder. These findings emphasize the essential function of genetic testing in children with chronic, treatment-refractory diarrhea and highlight the potential for excellent long-term outcomes with suitable supportive care.